Six-years survival and predictors of mortality after CABG using cold vs. warm blood cardioplegia in elective and emergent settings - Zeriouh, Mohamed; Heider, Ammar; Rahmanian, Parwis B.; Choi, Yeong-Hoon; Sabashnikov, Anton; Scherner, Maximillian; Popov, Aron-Frederik; Weymann, Alexander; Ghodsizad, Ali; Deppe, Antje-Christin; Kröner, Axel; Kuhn-Régnier, Ferdinand; et al. (Journal of cardiothoracic surgery, 2015)
The aim of this study was to determine whether intermittent warm blood cardioplegia (IWC) is associated with comparable myocardial protection compared to cold blood cardioplegia (ICC) in patients undergoing elective vs. emergent CABG procedures.
Gesehen am 23.07.2020